Study of Rare Semileptonic Bc+→D+νν- Decay in the Light-Cone Quark Model - Nisha Dhiman; Harleen Dahiya (Advances in High Energy Physics)
We study the exclusive semileptonic rare Bc+→D+νν¯ decay in the framework of light-cone quark model. The transition form factors f+(q2) and fT(q2) are evaluated in the timelike region using the analytic continuation method in q+=0 frame. The analytic solutions of these form factors are compared with the results obtained from the double pole parametric form. The branching ratio for Bc+→D+νν¯ decay is calculated and compared with the other theoretical model predictions. The predicted results in this model can be tested at the LHCb experiments in near future which will help in testing the unitarity of CKM quark mixing matrix, thus providing an insight into the phenomenon of CP violation.